Lithium metal negative electrode and preparation method thereof

By using a multi-layered lithium metal artificial protective layer in lithium metal batteries, the performance attenuation and safety problems caused by lithium dendrites growth and high electrolyte reactivity of lithium metal batteries are solved, and higher air stability is achieved. Uniform deposition and electrolyte barrier extend the cycle life of the battery and improve safety.

CN119419215APending Publication Date: 2025-02-11ZIJIN MINING GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411538583.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Lithium metal batteries have low efficiency and serious safety problems due to the growth of lithium dendrites and the high reactivity of lithium metal to electrolytes. Especially the brittleness and heterogeneity of the solid electrolyte interface SEI lead to battery performance attenuation and failure.

Method used

The lithium metal artificial protective layer adopts a multi-layer structure, including the surface fluorinated polymer, the inner polyether polymer and the lithium salt layer, is uniformly coated on the surface of the lithium metal belt through the preparation method to form a thickness of 1 to 15 μm. protective layer.

Benefits of technology

It significantly improves the air stability of lithium metal, regulates the uniform deposition of lithium metal, prevents the contact between electrolyte and lithium metal, completely eliminates the corrosion of the electrolyte on lithium metal, extends the cycle life of the battery and improves safety. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419215A_ABST
    Figure CN119419215A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium metal negative electrode and a preparation method thereof, and aims to solve the problems of performance degradation and safety of a lithium metal battery. The lithium metal negative electrode comprises a lithium metal strip and an artificial protection layer coating one side or two sides of the lithium metal strip; the artificial protective layer has a multi-layer structure and comprises a fluorinated polymer, a polyether polymer and a lithium salt layer, and the preparation method for the lithium metal negative electrode comprises the following steps and conditions: dissolving the polyether polymer in a solvent, stirring until the polyether polymer is completely dissolved, then adding a lithium salt, and uniformly stirring to obtain a precursor solution; adding the fluorinated polymer into a precursor solution, and heating and stirring until the polymer is completely dissolved and the solution is transparent to obtain a polymer solution; the lithium metal negative electrode has the advantages that the air stability is good, the lithium metal is uniformly deposited, the corrosion of the electrolyte to the lithium metal is thoroughly eliminated, and the lithium metal negative electrode is suitable for batch preparation of an existing lithium battery production line.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium metal negative electrode and a preparation method thereof. Background Art

[0002] Lithium metal has an ultra-high specific capacity (3860mAh / g), the lowest redox potential (-3.04V VS H+ / H2) and a light volume density (0.534g / cm3), so it is considered to be an ideal negative electrode for high-energy-density battery systems. However, the growth of lithium dendrites and the high reactivity of lithium metal to electrolytes lead to low coulombic efficiency of lithium metal batteries and serious safety issues. In recent years, many methods for stabilizing lithium metal have been reported, such as dual salt electrolytes, electrolyte additives, 3D skeleton structures, artificial protective layers, polymers or solid electrolyte layers, etc., but the solid electrolyte interface SEI is still a key issue in the practical application of lithium metal.

[0003] The SEI naturally formed on the surface of lithium metal is brittle and heterogeneous, and can be easily penetrated by lithium dendrites, resulting in performance degradation and safety issues of lithium metal batteries. After cycling, lithium dendrites will evolve into "dead lithium", causing the entire electrode to become a porous structure. Due to the continuous occurrence of side reactions, the electrolyte is eventually consumed, causing the battery to fail. To solve the above problems, researchers proposed to construct an artificial interface layer on the surface of lithium metal. The artificial interface layer can effectively alleviate the side reactions between lithium metal and the electrolyte, guide the uniform deposition of lithium metal, and inhibit the growth of lithium dendrites. At the same time, the artificial interface layer can also serve as a buffer layer to alleviate the cracking or pulverization caused by the volume expansion and stress concentration of lithium metal during the cycle, thereby reducing the interface impedance of the electrode.

[0004] Therefore, it is of great significance to develop a lithium metal negative electrode and a preparation method thereof. Summary of the invention

[0005] The task of the present invention is to overcome the deficiencies of the prior art and provide a lithium metal negative electrode and a preparation method thereof.

[0006] The task of the present invention is accomplished by the following technical solutions:

[0007] A lithium metal negative electrode, aimed at solving the problems of performance attenuation and safety of lithium metal batteries, comprises a lithium metal strip and an artificial protective layer coated on one side or both sides of the lithium metal strip; the artificial protective layer has a multilayer structure, including a fluorinated polymer, a polyether polymer and a lithium salt layer.

[0008] The preparation method for the lithium metal negative electrode comprises the following steps and conditions:

[0009] A. dissolving the polyether polymer in a solvent, stirring until completely dissolved, and then adding lithium salt and stirring evenly to obtain a precursor solution;

[0010] B. adding the fluorinated polymer to the precursor solution, heating and stirring until the polymer is completely dissolved and the solution is transparent, thereby obtaining a polymer solution;

[0011] C. Take a certain amount of polymer solution and evenly coat it on the surface of the lithium metal strip, dry it, and obtain a lithium metal negative electrode.

[0012] Compared with the prior art, the present invention has the following advantages or effects:

[0013] Because there is a multi-layer structure of the artificial protective layer of lithium metal and the surface fluorinated polymer has excellent hydrophobic properties, the air stability of lithium metal is greatly improved; at the same time, because the polyether polymer has excellent lithium affinity, the uniform deposition of lithium metal can be effectively regulated; in addition, because the artificial protective layer has good structural stability and can completely prevent the contact between the electrolyte and lithium metal, the corrosion of the electrolyte to the lithium metal can be completely eliminated; in addition, because the preparation method is also applicable to existing lithium battery production lines, it can also realize the batch preparation of modified lithium metal belts to meet the mass production needs of lithium metal batteries.

[0014] The % involved in this application document refers to mass percentage, and SEM is the abbreviation of scanning electron microscope, i.e. scanning electron microscope. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram of continuous coating of lithium metal strip on a lithium metal negative electrode and a preparation method thereof proposed in the present invention.

[0016] Figure 2 yes Figure 1 Schematic diagram of the left pole piece shown with continuous coating of lithium metal strip having strong air stability.

[0017] Figure 3 Schematic diagram of the assembled lithium metal soft-pack battery.

[0018] Figure 4 This is the SEM image of the lithium metal anode.

[0019] Figure 5 This is the SEM image of the lithium metal negative electrode after depositing 5mAh lithium metal. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0021] like Figures 1 to 5As shown, a lithium metal negative electrode, which addresses the problems of performance attenuation and safety of lithium metal batteries, includes a lithium metal strip and an artificial protective layer coated on one or both sides of the lithium metal strip; the artificial protective layer has a multilayer structure, including a fluorinated polymer, a polyether polymer and a lithium salt layer.

[0022] The lithium metal negative electrode of the present invention is further:

[0023] The multilayer structure of the artificial protective layer has a surface layer that is an enriched layer of fluorinated polymers and an inner layer that is a lithium-philic layer dominated by polyether polymers.

[0024] The fluorinated polymer includes any one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polytetrafluoroethylene, polychlorotrifluoroethylene, and polyvinyl fluoride.

[0025] The polyether polymer includes any one or more of trioxymethylene, polyoxymethylene, polyphenylene ether, chlorinated polyether, polyphenylene sulfide, and polyetheretherketone.

[0026] The lithium salt includes any one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), and lithium bis(trifluoromethylsulfonylimide).

[0027] The thickness of the artificial protective layer is 1 to 15 μm.

[0028] The thickness ratio of the artificial protective layer to the lithium metal strip is 1-15:20-150.

[0029] The preparation method for the lithium metal negative electrode comprises the following steps and conditions:

[0030] A. dissolving the polyether polymer in a solvent, stirring until completely dissolved, and then adding lithium salt and stirring evenly to obtain a precursor solution;

[0031] B. adding the fluorinated polymer to the precursor solution, heating and stirring until the polymer is completely dissolved and the solution is transparent, thereby obtaining a polymer solution;

[0032] C. Take a certain amount of polymer solution and evenly coat it on the surface of the lithium metal strip, dry it, and obtain a lithium metal negative electrode.

[0033] The preparation method for the lithium metal negative electrode may further be:

[0034] The polymer solution comprises components in the following proportions: polyether polymer, fluorinated polymer, lithium salt, and polyether polymer: fluorinated polymer: lithium salt = 40-85 wt. %: 20-65 wt. %: 0.5-3 wt. %.

[0035] The solvent accounts for 30 to 80 wt.% in the polymer solution.

[0036] The solvent is any one or more of ethylene glycol dimethyl ether, dimethyl carbonate, N,N-dimethylformamide, ethylene carbonate, fluoroethylene carbonate, dimethyl sulfoxide, and tetrahydrofuran.

[0037] The heating and stirring temperature in step B is 60-80°C.

[0038] The coating method of the polymer solution in step C is extrusion coating or gap coating.

[0039] The drying temperature of the polymer solution in step C is 25-80° C. and the drying time is 1-60 min. The prepared lithium metal negative electrode is cut into a specific size and assembled with the prepared positive electrode sheet to obtain a lithium metal battery after completing the steps of liquid injection, sealing, formation, secondary sealing, and capacity separation.

[0040] Example 1

[0041] (1) Weigh 12 g of trioxymethylene and dissolve it in 33 g of ethylene glycol dimethyl ether. After it is completely dissolved, add 0.12 g of lithium bis(trifluoromethylsulfonyl)imide and continue stirring until it is dissolved. Weigh 6 g of polytetrafluoroethylene and add it to the above solution. Stir at 60° C. for 5 h to obtain a clear and transparent polymer solution.

[0042] (2) The polymer solution is applied to the surface of the lithium metal strip by gap coating.

[0043] (3) The coated lithium metal strip is dried at 25° C., and then the reverse side is coated in the same steps as (2).

[0044] The prepared lithium metal negative electrode is cut into a specific size, and a battery is assembled with the prepared positive electrode sheet. After completing the steps of liquid injection, sealing, formation, secondary sealing, and capacity separation, the lithium metal battery is obtained.

[0045] like Figure 1 The lithium metal strip is continuously coated, and the obtained lithium metal negative electrode has strong air stability, such as Figure 2 Shown in the left pole piece. Figure 3 The assembled lithium metal soft-pack battery has a capacity retention rate of 98% after 80 cycles. Figure 4 is a SEM image of the lithium metal negative electrode, and the thickness of the single-sided artificial modification layer is about 4 μm. Figure 5 This is a SEM image of the lithium metal negative electrode after 5 mAh of lithium metal is deposited. The deposited lithium metal is uniform and dense.

[0046] Example 2

[0047] (1) Weigh 9 g of polyoxymethylene and dissolve it in a mixed solvent of 28 g of dimethyl carbonate and 2 g of N,N-dimethylformamide. After it is completely dissolved, add 0.1 g of lithium difluorooxalate borate and continue stirring until it is dissolved. Weigh 4 g of vinylidene fluoride hexafluoropropylene copolymer and add it to the above solution. Stir at 80°C for 3 hours to obtain a clear and transparent polymer solution.

[0048] (2) The polymer solution is applied to the surface of the lithium metal strip by gap coating.

[0049] (3) The coated lithium metal strip is dried at 80° C., and then the reverse side is coated in the same steps as (2).

[0050] The prepared lithium metal negative electrode is cut into a specific size, and assembled into a battery with the prepared positive electrode sheet. After completing the steps of liquid injection, sealing, formation, secondary sealing, and capacity separation, the lithium metal battery is obtained.

[0051] Example 3

[0052] (1) Weigh 10 g of trioxymethylene and dissolve it in a mixed solvent of 26 g of dimethyl carbonate and 3 g of dimethyl sulfoxide. After it is completely dissolved, add 0.09 g of lithium difluorooxalatoborate and 0.02 g of lithium bis(trifluoromethylsulfonyl)imide and continue stirring until dissolved. Weigh 5 g of vinylidene fluoride and add it to the above solution. Stir at 70°C for 4 h to obtain a clear and transparent polymer solution.

[0053] (2) The polymer solution is applied to the surface of the lithium metal strip by gap coating.

[0054] (3) The coated lithium metal strip is dried at 70° C., and then the reverse side is coated in the same steps as (2).

[0055] The prepared lithium metal negative electrode is cut into specific sizes and assembled with the prepared positive electrode sheet to obtain a lithium metal battery after completing the steps of liquid injection, sealing, formation, secondary sealing, and capacity separation.

[0056] Comparative Example 1

[0057] The pure lithium metal strip without artificial modification layer is directly cut into specific size, and assembled into battery with prepared positive electrode sheet, and the lithium metal battery is obtained after completing the steps of liquid injection, first sealing, formation, second sealing, and capacity separation.

[0058] As described above, the present invention can be better implemented. The above embodiments are only the best implementation methods of the present invention, but the implementation methods of the present invention are not limited by the above embodiments. Other changes, modifications, replacements, combinations, and simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A lithium metal negative electrode, which is characterized by: It comprises a lithium metal belt and an artificial protective layer coated on one side or both sides of the lithium metal belt; the artificial protective layer has a multi-layer structure, comprising a fluorinated polymer, a polyether polymer and a lithium salt layer.

2. The lithium metal negative electrode according to claim 1, characterized in that The multilayer structure of the artificial protective layer has a surface layer that is an enriched layer of fluorinated polymers and an inner layer that is a lithium-philic layer dominated by polyether polymers.

3. The lithium metal negative electrode according to claim 1 or 2, characterized in that The fluorinated polymer includes any one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polytetrafluoroethylene, polychlorotrifluoroethylene, and polyvinyl fluoride.

4. The lithium metal negative electrode according to claim 1 or 2, characterized in that The polyether polymer includes any one or more of trioxymethylene, polyoxymethylene, polyphenylene ether, chlorinated polyether, polyphenylene sulfide, and polyetheretherketone.

5. The lithium metal negative electrode according to claim 1, characterized in that The lithium salt includes any one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), and lithium bis(trifluoromethylsulfonylimide).

6. The lithium metal negative electrode according to claim 1, characterized in that The thickness of the artificial protective layer is 1 to 15 μm.

7. The lithium metal negative electrode according to claim 1 or 6, characterized in that The thickness ratio of the artificial protective layer to the lithium metal strip is 1-15:20-150.

8. A method for preparing the lithium metal negative electrode, characterized in that It includes the following steps and conditions: A. dissolving the polyether polymer in a solvent, stirring until completely dissolved, and then adding lithium salt and stirring evenly to obtain a precursor solution; B. adding the fluorinated polymer to the precursor solution, heating and stirring until the polymer is completely dissolved and the solution is transparent, thereby obtaining a polymer solution; C. Take a certain amount of polymer solution and evenly coat it on the surface of the lithium metal strip, dry it, and obtain a lithium metal negative electrode.

9. The method for preparing a lithium metal negative electrode according to claim 8, characterized in that The polymer solution includes the following components: Polyether polymer, fluorinated polymer, lithium salt and polyether polymer: fluorinated polymer: lithium salt = 40-85wt.%: 20-65wt.%: 0.5-3wt.%.

10. The method for preparing a lithium metal negative electrode according to claim 8, characterized in that The solvent accounts for 30 to 80 wt.% in the polymer solution.

11. The method for preparing a lithium metal negative electrode according to claim 8 or 10, characterized in that The solvent is any one or more of ethylene glycol dimethyl ether, dimethyl carbonate, N,N-dimethylformamide, ethylene carbonate, fluoroethylene carbonate, dimethyl sulfoxide, and tetrahydrofuran.

12. The method for preparing a lithium metal negative electrode according to claim 8, characterized in that The heating and stirring temperature in step B is 60-80°C.

13. The method for preparing a lithium metal negative electrode according to claim 8, characterized in that The coating method of the polymer solution in step C is extrusion coating or gap coating.

14. The method for preparing a lithium metal negative electrode according to claim 8, characterized in that The drying temperature of the polymer solution in step C is 25-80° C., and the drying time is 1-60 min.